Fab-to-fab and run-to-run variability in 130 nm and 65 nm CMOS technologies exposed to ultra-high TID. (1st January 2023) - Termo, G.; Borghello, G.; Faccio, F.; Michelis, S.; Koukab, A.; Sallese, J.-M.
Abstract: The discovery of a large fab-to-fab variability in the TID response of the CMOS technologies used in the design of ASICs for the particle detectors of the HL-LHC triggered a monitoring effort to verify the consistency of the CMOS production process over time. As of 2014, 22 chips from 3 different fabs in 130 nm CMOS technology and 11 chips from 2 different fabs in 65 nm CMOS technology have been irradiated to ultra-high doses, ranging from 100 Mrad(SiO2 ) to 1 Grad(SiO2 ). This unprecedented monitoring effort revealed significant fab-to-fab and run-to-run variability, both dependent on the characteristics of the MOS transistors.